2013
DOI: 10.1038/npp.2013.331
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Role of Transporter-Mediated Currents in the Depletion of Brain Serotonin Induced by Serotonin Transporter Substrates

Abstract: Serotonin (5-HT) transporter (SERT) substrates like fenfluramine and 3,4-methylenedioxymethamphetamine cause long-term depletion of brain 5-HT, while certain other substrates do not. The 5-HT deficits produced by SERT substrates are dependent upon transporter proteins, but the exact mechanisms responsible are unclear. Here, we compared the pharmacology of several SERT substrates: fenfluramine, d-fenfluramine, 1-(m-chlorophenyl)piperazine (mCPP) and 1-(m-trifluoromethylphenyl)piperainze (TFMPP), to establish re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 62 publications
3
37
0
Order By: Relevance
“…27 Acutely, substrates can account for higher concentrations of extracellular neurotransmitter than blockers, and substrate-induced inward current are correlated with long-term depletion of neurotransmitters in the brain. 28 …”
Section: Discussionmentioning
confidence: 99%
“…27 Acutely, substrates can account for higher concentrations of extracellular neurotransmitter than blockers, and substrate-induced inward current are correlated with long-term depletion of neurotransmitters in the brain. 28 …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18] Serotonin (5-hydroxytryptamine, 5-HT) antagonists enhance the susceptibility of DBA mice to S-IRA. 20,21 Recent clinical studies found fenfluramine to be effective as an add-on agent in the control of seizures in patients with Dravet syndrome, 22,23 which is difficult to treat and has a tragically high risk of SUDEP. 14,19 Fenfluramine is a drug that is known to enhance serotonergic neurotransmission by augmenting carrier-mediated synaptic release of 5-HT and by preventing reuptake.…”
Section: Introductionmentioning
confidence: 99%
“…Although substrate-induced currents through monoamine transporters are widely accepted [1215] and they have been implicated in neurotransmitter depletion in the brain [16], the physiological significance of such currents are still under debate [17, 18]. Recently, we showed that depolarization induced by serotonin (5HT) or S(+)3,4-methylenedioxymethamphetamine (MDMA, ecstasy) in skeletal muscle cells engineered to express the human serotonin transporter (hSERT) activates the L-type Ca 2+ channel Ca V 1.1 [19].…”
Section: Introductionmentioning
confidence: 99%